Opportunity Cost Analysis Sugarcane Cultivation in East Java – Indonesia - M Samsul Arifien; Teguh Soedarto; Hamidah Hendrarini; Eko Nurhadi (Nusantara Science and Technology Proceedings, 2024)
The opportunity cost for sugar cane farmers is the choice of cultivating sugar cane as a farming activity to support their livelihoods. Farming of other crops is not chosen, rejected, sacrificed. as opportunity costs. Farmers choose sugar cane as a commodity without choosing alternative crops that can be cultivated in the same location. Alternative crops are rice and corn, which can be competitors considering profits. To find out how much opportunity costs or sacrifices are made by sugar cane farmers, this research was carried out. The research method used is quantitative by calculating the income of sugar cane farmers and the income of rice and corn farming. The research was carried out in 4 districts of Sidorjo, Tulungagung, Ngawi, Situbodo, with a sample size of 120 respondents. The results of the research show that the Opportunity Cost value for sugar cane farmers in East Java is IDR 31,618,062 if the farmers plant rice and corn. Sugarcane farming is less profitable because it earns lower income, namely IDR 25,993,750,00.